Relationship between isometric peak force and maximal sprinting in elite track cyclists - Lewandowski, G.; McMullan, S. (Journal of Science and Cycling, 2023)
Isometric strength tests have been shown to provide valuable information on force-time characteristics in various sporting movements, including running, cycling and jumping (Kordiet al., 2017, 2020; Lum et al., 2020). There is a growing interest in monitoring off-bike isometric strength levels and examining their relationship with bike-specific metrics. In particular, it has been found that isometric strength measured on an adapted cycling ergometer is a predictor of maximal torque and peak power (Kordi et al., 2017, 2020). However, what is less known is the relationship between angle-specific isometric force-time characteristics measured using a strain gauge instrument fixed ona leg press and sprint cycling (6 sec maximal sprint) performance. The purpose of this research was to investigate the relationship between angle specific isometric strength and cycling specific metrics peak power and torque. We hypothesized that there would be a positive relationship with the ability to produce force in an isometric position and the ability to produce torque and power on a cycling ergometer. We propose that this setup would enable practitioners to track strength levels without requiring cycling-specific equipment and implement joint angle-specific isometric training in the weight room. Such information could help improve the effectiveness of strength training programs for cyclists.